Vindicating rights through the tortious liability of public authorities : themes and tensions in comparative perspective - Ryan, Desmond (Trinity College (Dublin, Ireland). School of Law, 2010)
The specific question addressed in this thesis is; to what degree are the core constituent ingredients in, and the outcomes of, domestic causes of action in the tortious liabihty of pubhc authorities being influenced by vindicatory pressures? This thesis is organised in the following way. In Part I, the key thematic tensions permeating the tortious liability of public authorities at present are identified and explored. Central to these is the ongoing difficulty in providing an "account" of the objectives of tort law. In this regard, emphasis is placed on what, it is argued, is an emerging theme in this area: that of vindication. The understandings of vindication emerging from the courts are identified and explored, and their relationship with and influence upon the archetypal goal of tort law - corrective justice - considered.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin